Implementasi Kebijakan Peraturan Gubernur Daerah Istimewa Yogyakarta Nomor 9 Tahun 2009 Tentang Pengelolaan Kawasan Waduk Sermo Kabupaten Kulon Progo - Henry Rahmananto; Cahyo Sasmito; Cakti ndra Gunawan (Universitas Swadaya Gunung Jati, 2022)
This research was conducted to find out how the implementation of the special regional governor's policy of Yogyakarta Number 9 of 2009 concerning the management of the Waduk Sermo Area. The research was conducted in Kulon Progo Regency with qualitative techniques. Determination of information is done by purposive sampling technique then the data is analyzed by reducing the data, presenting the data and drawing conclusions. The results show that the Waduk Sermo management policy as a whole has been running effectively, but there needs to be an increase in management intensity such as the development of various aspects of resources, organizing socialization and useful activities to support reservoir management activities, and optimizing coordination between the public works and spatial planning (PUPR) Office of Kulon Progo Regency and Serayu Opak River Basin Great Hall (BBWSSO). Supporting Factors There is good coordination between the Waduk Sermo management and the surrounding community, there is awareness and commitment with various parties in the utilization and preservation of the Waduk Sermo, and the availability of supporting facilities for the operational activities of the Waduk Sermo, while the inhibiting factor is that various technical violations are still found in the utilization of the Waduk Sermo, BBWSSO has limited authority in taking direct action against violations that occur, and it is difficult for the surrounding community to obtain permits to open rides or tourist attractions in the reservoir area.